Anti-reverse anode catalyst layer and preparation method thereof, membrane electrode and fuel cell

By designing a transition layer and a gradient anode catalyst layer in the anode catalyst layer of a fuel cell, and utilizing the hydrogen storage capacity of Pd and the high catalytic activity of Pt, the problems of catalyst corrosion and high cost caused by the reverse polarity phenomenon in fuel cells are solved, thereby improving the stability and efficiency of fuel cells.

CN121076151APending Publication Date: 2025-12-05DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511000441.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

In existing fuel cell technologies, the anode catalyst layer is prone to corrosion and is costly under reverse polarity, and existing strategies cannot effectively prevent reverse polarity, resulting in limited fuel cell stability and efficiency.

Method used

A reverse polarity resistant anode catalyst layer is designed, comprising a transition layer and a gradient anode catalyst layer. The transition layer consists of a p-WO3 film, a deposition layer, and a sulfonic acid group ion polymer. The deposition layer contains Pd and Pt nanoparticles. The content of Pd/C and Pt/C hybrid catalysts in the gradient anode catalyst layer shows an increasing and decreasing trend, respectively. Through the synergistic effect of Pd's hydrogen storage buffer and Pt's high catalytic activity, a multi-layered protective barrier is formed.

Benefits of technology

It improves the stability and catalytic activity of fuel cells under fuel shortage conditions, extends their service life, reduces the amount of precious metals used, and lowers manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121076151A_ABST
    Figure CN121076151A_ABST
Patent Text Reader

Abstract

The invention provides an anti-reverse anode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell, and belongs to the field of fuel cells. The transition layer comprises a p-WO3 film, a deposition layer deposited on the surface of the p-WO3 film and an ionic polymer which is dispersed in the deposition layer and contains a sulfonic acid group; pd and Pt nano particles are contained in the deposition layer; and the gradient anode catalyst layer is arranged on one side of the transition layer and contains Pd / C and Pt / C hybrid catalysts, and the Pd content in the Pd / C and Pt / C hybrid catalysts is in an increasing trend and the Pt content is in a decreasing trend along the flowing direction of hydrogen in the membrane electrode. The anode catalyst layer with different Pd / C content hybridized non-uniform grid distribution gradient is designed, hydrogen is automatically supplemented at the position close to an outlet where fuel shortage may occur, antipole is actively prevented, and low cost, high performance, long durability and antipole resistance are shown under various working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of fuel cells, in particular to an anti-reversal anode catalyst layer, a preparation method thereof, a membrane electrode and a fuel cell. BACKGROUND

[0002] In recent years, the global energy crisis and environmental pollution problems have become increasingly serious, prompting countries around the world to actively seek renewable energy solutions. Hydrogen energy, with its high energy density, clean environmental protection (theoretical reaction product is only water) and wide source characteristics, has become the focus of the new energy field. In the field of new energy vehicles, fuel cells play a key role in the efficient use of chemical bonds due to their high efficiency and fuel flexibility. However, the large-scale application of fuel cell technology still faces two major challenges: high catalyst cost and insufficient catalyst durability. The membrane electrode assembly (MEA) of the proton exchange membrane fuel cell (PEMFC) is prone to reversal under frequent start / stop cycles and fuel shortage conditions, causing fatal damage to the stack. The main reason for reversal failure is the corrosion of the carbon support in the Pt / C catalyst and the insufficient supply of hydrogen. In particular, near the anode outlet, due to uneven hydrogen distribution, local hydrogen deficiency causes the necessary oxidation reaction to release electrons and protons to be unable to maintain, thereby breaking the charge balance. To make up for this imbalance, water, carbon and other substances in the anode catalyst layer may undergo oxidation reactions to produce protons and release electrons, ultimately triggering anode reversal.

[0003] In view of the reversal problem, existing technologies have proposed various countermeasures. One solution is to add an oxygen evolution catalyst, such as IrO2, to the anode catalyst layer to slow down the corrosion of the carbon support when reversal occurs. IrO2, with its high activity, excellent corrosion resistance and stability, can to some extent alleviate the damage to the catalyst layer caused by reversal. However, this solution has significant drawbacks: first, IrO2 is a rare and expensive noble metal material, limiting its commercial application in proton exchange membrane catalyst layers; second, this method can only reduce damage when reversal occurs, but cannot fundamentally prevent reversal from occurring, with limited anti-reversal level. Another existing technology focuses on system management, monitoring voltage, current density distribution, local temperature changes or real-time detection of anode outlet CO2 content through additional equipment to prevent reversal. Although this system management strategy can provide additional safety, its complexity and significant cost increase make it difficult to apply in practice. Therefore, how to simultaneously improve the catalytic activity and anti-reversal ability of the anode catalyst layer is a technical problem that needs to be solved. SUMMARY

[0004] The present application provides an anti-reversal anode catalyst layer, a preparation method thereof, a membrane electrode and a fuel cell to solve the technical problem of how to simultaneously improve the catalytic activity and anti-reversal ability of the anode catalyst layer.

[0005] In a first aspect, the embodiments of the present application provide an anti-reverse anode catalyst layer, comprising: a transition layer, comprising a p-WO3 film, a deposition layer deposited on at least part of the surface of the p-WO3 film, and an ionic polymer containing sulfonic acid groups dispersed in the deposition layer; the deposition layer containing Pd nanoparticles and Pt nanoparticles; and a gradient anode catalyst layer arranged on one side of the transition layer, containing Pd / C and Pt / C hybrid catalysts, along the flow direction of hydrogen in the membrane electrode, the mass content of Pd in the Pd / C and Pt / C hybrid catalysts showing an increasing trend, and the mass content of Pt in the Pd / C and Pt / C hybrid catalysts showing a decreasing trend.

[0006] Optionally, in the transition layer, the mass ratio of the Pd nanoparticles to the Pt nanoparticles is 1:(1-2).

[0007] Optionally, the thickness of the transition layer is less than or equal to 1.0 μm.

[0008] Optionally, in the gradient anode catalyst layer, along the flow direction of hydrogen in the membrane electrode, the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the starting position is 1:(2-4).

[0009] Optionally, in the gradient anode catalyst layer, along the flow direction of hydrogen in the membrane electrode, the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the end position is (2-4):1.

[0010] Optionally, the thickness of the gradient anode catalyst layer is 2 μm-4 μm.

[0011] In a second aspect, the present application provides a preparation method of the anti-reverse anode catalyst layer according to any one of the embodiments of the first aspect, the method comprising: obtaining a WO3 film; activating the WO3 film to generate oxygen vacancies in the WO3 lattice of the WO3 film, to obtain a p-WO3 film; depositing Pd nanoparticles and Pt nanoparticles on at least part of the surface of the p-WO3 film to obtain a deposition layer; dispersing an ionic polymer containing sulfonic acid groups into the deposition layer to obtain a transition layer; A hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is sprayed on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and the mass content of Pd in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually increased, and the mass content of Pt in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually decreased along the flow direction of hydrogen in the membrane electrode, to form a gradient anode catalyst layer with gradually increasing mass content of Pd and gradually decreasing mass content of Pt along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, to obtain an anti-reverse anode catalyst layer.

[0012] Optionally, the WO3 film is obtained by: mixing WO3 nano powder with anhydrous ethanol to obtain WO3 slurry; coating the WO3 slurry on a base film and drying to obtain a WO3 film.

[0013] Optionally, the mass ratio of the WO3 nano powder to the anhydrous ethanol is 1:(1-10).

[0014] Optionally, the activation is performed by plasma surface treatment.

[0015] Optionally, the deposition of Pd nano particles and Pt nano particles on at least part of the surface of the p-WO3 film to obtain a deposition layer comprises: adsorbing Pd precursor and Pt precursor to the surface of the p-WO3 film under vacuum conditions to obtain a p-WO3 film containing Pd precursor and Pt precursor, wherein the Pd precursor is palladium chloride, and the Pt precursor is trimethyl (methylcyclopentadienyl) platinum; purging the p-WO3 film containing Pd precursor and Pt precursor in an inert gas; carrying out adsorption reaction of oxygen precursor with the Pd precursor and the Pt precursor in the p-WO3 film to obtain a deposition layer containing Pd nano particles and Pt nano particles, wherein the oxygen precursor is O2 plasma.

[0016] Optionally, the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is sprayed on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and the mass content of Pd in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually increased and the mass content of Pt in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually decreased along the flow direction of hydrogen in the membrane electrode to form a gradient anode catalyst layer with the mass content of Pd gradually increasing and the mass content of Pt gradually decreasing along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, thereby obtaining a reverse-pole-resistant anode catalyst layer, comprising: Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin and solvent are mixed to obtain a first catalyst ink and a second catalyst ink, respectively, the Pd concentration of the first catalyst ink is greater than the Pd concentration of the second catalyst ink, and the Pt concentration of the first catalyst ink is less than the Pt concentration of the second catalyst ink; The first catalyst ink and the second catalyst ink are sprayed on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode using a double-nozzle ultrasonic atomization spraying system, and during the spraying process, the spraying flow rate of the first catalyst ink is increased and the spraying flow rate of the second catalyst ink is decreased, so as to form a gradient anode catalyst layer with the mass content of Pd gradually increasing and the mass content of Pt gradually decreasing along the flow direction of hydrogen in the membrane electrode on one side of the transition layer; The gradient anode catalyst layer is dried and cured to obtain a reverse-pole-resistant anode catalyst layer.

[0017] Optionally, the drying temperature is 70-90°C, and the drying time is 20-40 min.

[0018] Optionally, the curing temperature is 120-160°C, and the curing time is 5-15 min.

[0019] Optionally, in the first catalyst ink, the mass ratio of Pd to Pt is (2-4):1. In the second catalyst ink, the mass ratio of Pd to Pt is 1:(2-4).

[0020] In a third aspect, the application provides a membrane electrode, which comprises a proton exchange membrane, a cathode catalyst layer, a reverse-pole-resistant anode catalyst layer according to any one of the first aspect and a gas diffusion layer arranged in sequence, and the transition layer of the reverse-pole-resistant anode catalyst layer is adjacent to the proton exchange membrane.

[0021] Optionally, the Pt / C catalyst loading of the cathode catalyst layer is 0.3 mgPt / cm 2 ~0.5mg Pt / cm 2 .

[0022] In a fourth aspect, the present application provides a fuel cell comprising the reverse-sparking resistant anode catalytic layer according to any one of the embodiments of the first aspect, or the membrane electrode according to the third aspect.

[0023] Compared with the prior art, the above technical solution provided by the embodiments of the present application has the following advantages: The embodiments of the present application provide a reverse-sparking resistant anode catalytic layer, comprising: a transition layer, comprising a p-WO3 film, a deposition layer deposited on at least part of the surface of the p-WO3 film, and an ionic polymer containing sulfonic acid groups dispersed in the deposition layer; the deposition layer contains Pd nanoparticles and Pt nanoparticles; a gradient anode catalyst layer is arranged on one side of the transition layer and contains Pd / C and Pt / C hybrid catalysts, and along the flow direction of hydrogen in the membrane electrode, the mass content of Pd in the Pd / C and Pt / C hybrid catalysts shows an increasing trend, and the mass content of Pt in the Pd / C and Pt / C hybrid catalysts shows a decreasing trend. The structure of the reverse-sparking resistant anode catalytic layer is reasonably designed. First, the transition layer buffers the hydrogen storage of Pd, enhances the electron conduction of WO3, and rapidly transports the protons of the sulfonic acid group, forming a "trinity" protective barrier, preferentially activating the redox reaction of WO3 in the initial reverse-sparking stage, sacrificially consuming the reverse-sparking current, and protecting the Pt / C main catalyst; second, along the flow direction of hydrogen in the membrane electrode, the content of Pd in the gradient anode catalyst layer shows an increasing trend, and the content of Pt shows a decreasing trend. This gradient design aims to adapt to the actual situation of gradually decreasing hydrogen flow and ensure high catalytic activity throughout the hydrogen flow path. In the inlet area with a large hydrogen flow, the Pt / C catalyst has a high proportion to fully utilize the high catalytic activity of Pt; while in the outlet area with a small hydrogen flow, the Pd / C catalyst has a high proportion to utilize the hydrogen storage capacity of Pd to supplement hydrogen and prevent reverse-sparking; finally, the Pd nanoparticles in the transition layer act as a hydrogen storage buffer layer, which can release the stored hydrogen when the hydrogen concentration decreases; and the gradient distribution of Pd / C catalyst in the gradient anode catalyst layer can automatically supplement hydrogen under fuel shortage. The two layers complement each other in hydrogen storage and hydrogen supply mechanisms, ensuring the stable operation of the fuel cell under fuel shortage, thereby improving the catalytic activity and reverse-sparking resistance of the anode catalytic layer. BRIEF DESCRIPTION OF DRAWINGS

[0024] The accompanying drawings, which are incorporated herein and form part of the specification, illustrate embodiments consistent with the present application and, together with the description, further serve to explain the principles of the application.

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the accompanying drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, those skilled in the art can obtain other drawings according to these drawings without any creative effort.

[0026] Figure 1 A structural schematic diagram of an anti-reverse-polarization anode catalytic layer provided by the embodiments of the present application; Figure 2 A flowchart of a preparation method of an anti-reverse-polarization anode catalytic layer provided by the embodiments of the present application; Figure 3 A fuel cell single cell test polarization curve provided by the embodiment 4 and the comparative example 1 of the present application; Figure 4 A fuel cell single cell simulation reverse polarization comparison diagram provided by the embodiment 4 and the comparative example 1 of the present application; Reference signs: 1-anti-reverse-polarization anode catalytic layer, 11-transition layer, 12-gradient anode catalyst layer, 2-proton exchange membrane, 3-cathode catalytic layer, 4-gas diffusion layer. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present application more clear, the technical solutions of the embodiments of the present application will be described clearly and completely in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without any creative effort fall within the scope of protection of the present application.

[0028] Various embodiments of the present application can exist in the form of a range; it should be understood that the description in the form of a range is merely for the convenience and brevity, and should not be understood as a hard limit on the scope of the present application; therefore, it should be considered that the described range has specifically disclosed all possible sub-ranges and single values in the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers in the described range, such as 1, 2, 3, 4, 5 and 6, regardless of the range. In addition, whenever a numerical range is indicated in this document, it refers to any cited number (fraction or integer) in the indicated range.

[0029] In addition, in the description of the present application, the terms "comprise", "contain" and the like mean "comprise but not limited to". In this paper, such as "first" and "second" and other relational terms are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between the entities or operations. In this paper, "and / or", the association relationship between the associated objects, indicates that there can be three kinds of relationships, for example, A and / or B, which can represent the following cases: A exists alone, A and B exist together, and B exists alone. Where A and B can be singular or plural. In this paper, "at least one" means one or more, and "multiple" means two or more. "At least one", "at least one of the following" or similar expressions mean any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can represent a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, where a, b, and c can be single or multiple. "Parts representation method" such as weight parts, mass parts, etc. represents the proportional relationship between the components. In the proportional relationship involved in this paper, the parameters that need to be described by proportion should be understood as the front item of the proportional formula in the order of description, and the proportional number should be understood as the latter item of the proportional formula, for example, the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should be in the proportional formula according to the description order and the proportional number one by one, that is, the mass of substance A: the mass of substance B: the mass of substance C = 1:2:3.

[0030] Unless otherwise specified, the various raw materials, reagents, instruments and equipment used in this application can be purchased or prepared by existing methods.

[0031] Figure 1 The structure diagram of the anti-reverse anode catalytic layer provided in the embodiments of the present application.

[0032] As Figure 1 shown, the present application provides an anti-reverse anode catalytic layer 1, comprising: a transition layer 11, comprising a p-WO3 film, a deposition layer deposited on at least part of the surface of the p-WO3 film, and an ionic polymer containing sulfonic acid groups dispersed in the deposition layer; the deposition layer contains Pd nanoparticles and Pt nanoparticles; and The gradient anode catalyst layer 12 is arranged on one side of the transition layer 11 and contains Pd / C and Pt / C hybrid catalysts. The mass content of Pd in the Pd / C and Pt / C hybrid catalysts shows an increasing trend along the flow direction of hydrogen in the membrane electrode, and the mass content of Pt in the Pd / C and Pt / C hybrid catalysts shows a decreasing trend.

[0033] The transition layer is a key component of the anti-reverse anode catalyst layer, and its design aims to improve the stability and performance of the fuel cell under fuel shortage conditions through multiple mechanisms. Specifically, the transition layer mainly functions in the following aspects: (1) "Trinity" protective barrier: Pd nanoparticles in the transition layer have excellent hydrogen storage capacity and can release stored hydrogen when the hydrogen concentration decreases, thereby slowing down the occurrence of reverse polarization. This hydrogen storage buffer helps maintain the stable operation of the fuel cell under fuel shortage conditions. At the same time, the p-WO3 layer as the base of the transition layer produces oxygen vacancies after activation treatment, improving the electronic conductivity.

[0034] (2) Prior activation of the redox reaction of WO3: As an anode catalyst carrier, WO3 in the transition layer can preferentially undergo a redox reaction at the initial stage of reverse polarization, sacrificially consuming reverse polarization current, avoiding the corrosion problem caused by traditional carbon carriers. At the same time, WO3 can produce H x WO3, H x The decomposition of WO3 can provide additional hydrogen ions and electrons, which can avoid the shortage of anode hydrogen supply and thus avoid the occurrence of reverse polarization, thereby avoiding the serious corrosion of the anode catalyst and protecting the Pt / C main catalyst from damage by reverse polarization.

[0035] (3) Ultra-thin design: The thickness of the transition layer is controlled to be below 1 μm, aiming to reduce the internal resistance while ensuring that Pd and Pt nanoparticles can fully contact the p-WO3 film to form an effective protective barrier. Ultra-thin design helps improve the overall performance of the fuel cell.

[0036] The gradient anode catalyst layer is the main place for catalyzing hydrogen oxidation reaction in the fuel cell, and its design directly affects the performance and stability of the fuel cell. In the anti-reverse anode catalyst layer, the gradient anode catalyst layer mainly functions in the following aspects: (1) Gradient distribution of Pd / C and Pt / C hybrid catalyst: Along the flow direction of hydrogen in the membrane electrode, the Pd content in the gradient anode catalyst layer shows an increasing trend, while the Pt content shows a decreasing trend. The hydrogen storage / release process in the Pd lattice, when Pd is in the H2 atmosphere, it can spontaneously react with H to form unstable Pd−H bonds and store H in the lattice, when the surrounding H2 concentration decreases, the Pd−H bond breaks and the stored H is released. This gradient design aims to adapt to the actual situation of gradually decreasing hydrogen flow, in the inlet area where the hydrogen flow is large, the Pt / C catalyst has a high proportion, to make full use of the high catalytic activity of Pt; while in the outlet area where the hydrogen flow is small, the Pd / C catalyst has a high proportion, to make use of the hydrogen storage capacity of Pd to supplement hydrogen and prevent the occurrence of reverse polarization.

[0037] (2) Improve hydrogen utilization: By designing a gradient anode catalyst layer with different Pd / C content hybrid uneven grid distribution, when Pd is in the H2 atmosphere, it can spontaneously react with H to form unstable Pd−H bonds and store H in the lattice. This design helps to improve the utilization of hydrogen, reduce the emission of unreacted hydrogen, and thus improve the overall efficiency of the fuel cell.

[0038] (3) Save Pd usage: The gradient design allows the use of a higher proportion of Pd / C catalyst in the outlet area, and a lower proportion of Pd / C catalyst in the inlet area. This design helps to save expensive Pd resources and reduce the manufacturing cost of the fuel cell.

[0039] The transition layer and the gradient anode catalyst layer play a crucial role in the anti-reverse polarization anode catalyst layer. They complement and enhance each other through their unique mechanisms, and together improve the stability, performance and service life of the fuel cell under fuel shortage conditions. Specifically, the synergistic effect of the transition layer and the gradient anode catalyst layer mainly manifests in the following aspects: (1) Complementary hydrogen storage and hydrogen supply mechanisms: Pd nanoparticles in the transition layer act as a hydrogen storage buffer layer, which can release stored hydrogen when the hydrogen concentration decreases; while the gradient distribution of Pd / C catalyst in the gradient anode catalyst layer can automatically supplement hydrogen under fuel shortage conditions. These two layers work together through complementary hydrogen storage and hydrogen supply mechanisms to ensure stable operation of the fuel cell under fuel shortage conditions.

[0040] (2) Enhanced electron and proton transport: The p-WO3 film and sulfonic acid groups in the transition layer enhance the transport of electrons and protons, respectively; while the high-activity Pt / C and Pd / C catalysts in the gradient anode catalyst layer promote the oxidation of hydrogen. These two layers work together through enhanced electron and proton transport to improve the reaction efficiency and output performance of the fuel cell.

[0041] (3) Prolong the life of fuel cell: WO3 in the transition layer preferentially undergoes redox reaction at the initial stage of reverse polarity, sacrificially consumes reverse polarity current, and protects the main catalyst Pt / C from damage; and the gradient design in the gradient anode catalyst layer reduces the reverse polarity phenomenon caused by fuel shortage. These two layers prolong the life of the fuel cell through different mechanisms.

[0042] In some embodiments, in the transition layer, the mass ratio of the Pd nanoparticles to the Pt nanoparticles is 1:(1-2).

[0043] The mass ratio of Pd nanoparticles to Pt nanoparticles in the ultra-thin transition layer is limited to 1:(1-2), aiming to balance the hydrogen storage capacity of Pd and the catalytic activity of Pt. Pd has a high hydrogen storage capacity and can release stored hydrogen when hydrogen is insufficient, thereby slowing down the reverse polarity phenomenon; while Pt is the main catalyst responsible for the oxidation of hydrogen. By adjusting this ratio, the catalytic efficiency can be ensured while enhancing the reverse polarity resistance of the catalyst layer. For example, the mass ratio of Pd to Pt nanoparticles in the transition layer can be 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, etc.

[0044] In some embodiments, the thickness of the transition layer 11 is less than or equal to 1.0 μm.

[0045] The transition layer needs to be thin enough to reduce the obstruction to proton transport, while ensuring that Pd and Pt nanoparticles can fully contact the p-WO3 film to form an effective "trinity" protective barrier. If the thickness of the transition layer is > 1 μm, it will increase the resistance to proton transport, affecting the performance of the fuel cell. For example, the thickness of the transition layer can be 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, etc.

[0046] In some embodiments, in the gradient anode catalyst layer 12, along the flow direction of hydrogen in the membrane electrode, the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the starting position is 1:(2-4).

[0047] In some embodiments, in the gradient anode catalyst layer 12, along the flow direction of hydrogen in the membrane electrode, the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the end position is (2-4):1.

[0048] The starting position Pd:Pt = 1:(2-4), near the hydrogen inlet, the hydrogen supply is sufficient, at this time the catalytic effect of Pt is more important, so the content of Pt is relatively high. The end position Pd:Pt = (2-4):1, near the hydrogen outlet, the hydrogen concentration gradually decreases, at this time the hydrogen storage and release ability of Pd becomes more critical, so the content of Pd gradually increases. This gradient design can ensure that the catalytic layer can maintain high catalytic activity and anti-reverse polarity ability throughout the hydrogen flow path. For example, in the gradient anode catalyst layer, the mass ratio of Pd nanoparticles to Pt nanoparticles at the starting position can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc., and the mass ratio of Pd nanoparticles to Pt nanoparticles at the end position can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc.

[0049] In some embodiments, the thickness of the gradient anode catalyst layer 12 is 2-4 μm.

[0050] Limiting the thickness of the gradient anode catalyst layer to 2-4 μm can ensure that the catalytic layer has sufficient catalyst loading to maintain efficient catalytic reaction. At the same time, if the thickness of the catalytic layer is higher than 4 μm, it will increase the mass transfer resistance and affect the transmission efficiency of hydrogen and protons. For example, the thickness of the gradient anode catalyst layer can be 2 μm, 2.2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.

[0051] Figure 2 A flowchart of a preparation method of an anti-reverse polarity anode catalyst layer provided in an embodiment of the present application.

[0052] Based on a general inventive concept, as shown in Figure 2 The present application provides a preparation method of an anti-reverse polarity anode catalyst layer according to any one of the above embodiments, which comprises: S1, obtaining a WO3 film; S2, activating the WO3 film to generate oxygen vacancies in the WO3 lattice of the WO3 film, to obtain a p-WO3 film; S3, depositing Pd nanoparticles and Pt nanoparticles on at least part of the surface of the p-WO3 film to obtain a deposition layer; S4, dispersing an ionic polymer containing sulfonic acid groups into the deposition layer to obtain a transition layer; S5, spraying the hybrid catalyst ink containing the Pt / C catalyst and the Pd / C catalyst on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, gradually increasing the mass content of Pd in the hybrid catalyst ink containing the Pt / C catalyst and the Pd / C catalyst and gradually reducing the mass content of Pt in the hybrid catalyst ink containing the Pt / C catalyst and the Pd / C catalyst along the flow direction of hydrogen in the membrane electrode to form a gradient anode catalyst layer with gradually increasing mass content of Pd and gradually decreasing mass content of Pt along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, thereby obtaining an anti-reverse anode catalyst layer.

[0053] In some embodiments, the WO3 film is obtained by: S101, mixing WO3 nano powder and anhydrous ethanol to obtain a WO3 slurry; S102, coating the WO3 slurry on a substrate film and drying to obtain a WO3 film.

[0054] In some embodiments, the mass ratio of the WO3 nano powder to the anhydrous ethanol is 1:(1-10).

[0055] It should be noted that the substrate film can be a polyimide film, and the substrate film can be removed by transfer printing during hot pressing to prepare the MEA.

[0056] Limiting the mass ratio of the WO3 nano powder to the anhydrous ethanol to 1:(1-10) can ensure that the WO3 nano powder is fully dispersed in the anhydrous ethanol, and on the other hand, can ensure that the volatilization time of ethanol is not too long during the subsequent drying process. For example, the mass ratio of the WO3 nano powder to the anhydrous ethanol can be 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, etc.

[0057] In some embodiments, the activation is performed by plasma surface treatment.

[0058] In the above embodiments, a large number of oxygen vacancies are generated in the WO3 lattice during the plasma surface treatment, thereby increasing the Fermi energy level of the WO3 thin film and reducing the band gap energy. At the same time, due to the reduced band gap energy, the activated p-WO3 thin film has the same low resistance property as n-type semiconductors. Therefore, the plasma surface treatment can solve the problem of large resistance of WO3, and at the same time, the plasma surface treatment breaks the inert state of WO3, thereby improving the surface reactivity of WO3, and facilitating the deposition of Pt. Therefore, the plasma surface treatment on the WO3 layer can compensate for the problem that the low conductivity of metal oxides may cause the initial performance to decrease.

[0059] In some embodiments, the plasma gas source of the plasma surface treatment includes one or more of O2, Ar, H2, and N2, and the plasma surface treatment includes the following parameters: the flow rate of the plasma gas source is 10-30 sccm, the RF plasma power is 150-200 W, and the chamber pressure is ≤30 mTorr.

[0060] In the above embodiments, the RF power directly affects the plasma concentration, and the flow rate of the plasma gas source, the RF plasma power, and the chamber pressure are controlled to ensure sufficient activation of the WO3 film. For example, the flow rate of the plasma gas source can be 10, 15, 20, 25, 30 sccm, etc., the RF plasma power can be 150, 160, 170, 180, 190, 200 W, etc., and the chamber pressure can be 10, 15, 20, 25, 30 mTorr, etc.

[0061] In some embodiments, the deposition of Pd nanoparticles and Pt nanoparticles on at least part of the surface of the p-WO3 film to obtain a deposition layer includes: S301, under vacuum conditions, adsorbing Pd precursor and Pt precursor onto the surface of the p-WO3 film to obtain a p-WO3 film containing Pd precursor and Pt precursor, wherein the Pd precursor is palladium chloride and the Pt precursor is trimethyl (methylcyclopentadienyl) platinum; S302, purging the p-WO3 film containing Pd precursor and Pt precursor in an inert gas; S303, adsorbing oxygen precursor with Pd precursor and Pt precursor in the p-WO3 film to obtain a deposition layer containing Pd nanoparticles and Pt nanoparticles; the oxygen precursor is O2 plasma.

[0062] The plasma enhanced atomic layer deposition device (PEALD) mainly consists of a deposition chamber, a plasma source, a reaction gas supply system, and a control system.

[0063] In a plasma enhanced atomic layer deposition (PEALD) process, trimethyl(methylcyclopentadienyl) platinum (MeCpPtMe3) and palladium chloride (PdCl2) precursors are introduced into a deposition chamber in a pulsed manner with high-speed argon (Ar) gas, so that they are saturatedly adsorbed on the surface of a p-WO3 film. Subsequently, O2 plasma is excited to react with the adsorbed precursors: MeCpPtMe3 is decomposed to generate Pt nanoparticles, and the released methyl and cyclopentadienyl ligands are oxidized to CO2 and H2O; PdCl2 is reduced to Pd and releases Cl2. By cyclically performing the steps of "precursor adsorption → Ar gas purge → plasma oxidation reaction", a uniform and dense Pt / Pd nanoparticle layer can be deposited layer by layer, and the specific reaction formula is as follows: MeCpPtMe3 + O2 (plasma) → Pt↓ + CO2↑ + H2O↑ + volatile organic compounds, PdCl2 + O2 (plasma) → Pd↓ + Cl2↑.

[0064] The deposition method provided by the present application has the following advantages: the reaction can be efficiently carried out at a low temperature of 120-160°C, the generated metal layer has high purity and strong adhesion, and the size of the nanoparticles can be accurately controlled to be sub-nanometer; at the same time, through layer-by-layer deposition at the atomic layer level, the amount of noble metal can be accurately controlled to reduce the cost, and the exposure of the catalytic active sites can be maximized; in addition, strong chemical bonding is formed between the nanoparticles and the p-WO3 substrate, thereby improving the durability and corrosion resistance of the transition layer. Therefore, the transition layer synthesized by the technology has the advantages of low cost, high performance and long service life in the application of fuel cell anti-reverse polarity.

[0065] In some embodiments, the temperature of the deposition chamber is 120-160°C, and the temperature of the platinum precursor is maintained at 65-85°C.

[0066] In the above embodiments, the temperature of the precursor affects the deposition rate. Controlling the temperature of the deposition chamber and the temperature of the platinum precursor can not only ensure the deposition rate of platinum, but also avoid the decomposition failure of the platinum precursor. At the same time, the temperature of the deposition chamber is also the deposition temperature. For example, the temperature of the deposition chamber can be 120°C, 130°C, 140°C, 150°C, 160°C, etc., and the temperature of the platinum precursor can be maintained at 65°C, 70°C, 75°C, 80°C, 85°C, etc.

[0067] In some embodiments, the inert gas is Ar gas, and the purging time is 60-120 s.

[0068] Thus, in some embodiments of the present application, a p-WO3 film is first obtained by activating a WO3 film, and then Pt and Pd nanoparticles are deposited on the p-WO3 film by means of plasma surface treatment technology, while dispersing an ionic polymer containing sulfonic acid groups in the deposited layer, to finally form an ultra-thin transition layer with a thickness of ≤1.0 μm. This ultra-thin transition layer not only reduces the obstruction to proton transmission, but also, due to the simultaneous presence of Pt and Pd nanoparticles and sulfonic acid groups, can construct a "trinity" protective barrier through the hydrogen storage buffering effect of Pd, the enhancement effect on the electronic conduction of WO3, and the rapid proton transmission effect of the sulfonic acid groups, thereby preferentially activating the redox reaction of WO3 in the initial stage of reverse polarization and protecting the Pt / C main catalyst by sacrificial consumption of the reverse polarization current.

[0069] In some embodiments, the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is sprayed on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and the mass content of Pd in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually increased, and the mass content of Pt in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst is gradually decreased along the flow direction of hydrogen in the membrane electrode, to form a gradient anode catalyst layer with an increasing gradient of Pd mass content and a decreasing gradient of Pt mass content along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, to obtain a reverse polarization-resistant anode catalyst layer, comprising: S501, mixing Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin and solvent to obtain first catalyst ink and second catalyst ink, respectively, the Pd concentration of the first catalyst ink is greater than the Pd concentration of the second catalyst ink, and the Pt concentration of the first catalyst ink is less than the Pt concentration of the second catalyst ink; S502, using a double-nozzle ultrasonic atomization spraying system, spraying the first catalyst ink and the second catalyst ink on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and in the process of spraying, the spraying flow of the first catalyst ink is increased, and the spraying flow of the second catalyst ink is decreased, to form a gradient anode catalyst layer with an increasing gradient of Pd mass content and a decreasing gradient of Pt mass content along the flow direction of hydrogen in the membrane electrode on one side of the transition layer; S503, drying and curing the gradient anode catalyst layer to obtain a reverse polarization-resistant anode catalyst layer.

[0070] It should be noted that the in-situ storage and release of the energy in the palladium lattice is due to the hydrogen storage / release process in the Pd lattice. When Pd is in the H2 atmosphere, it can spontaneously react with H to form unstable Pd-H bonds and store H in the lattice. When the surrounding H2 concentration decreases, the Pd-H bonds break and the stored H is released. By designing a hybrid heterogeneous mesh distribution gradient anode catalyst layer with different Pd / C contents, H2 can be automatically supplemented at the location close to the outlet where fuel shortage may occur. This greatly improves the utilization of hydrogen, while the gradient design also saves the amount of Pd and eliminates the reverse polarity caused by fuel shortage.

[0071] In some embodiments, the drying temperature is 70-90°C, and the drying time is 20-40 min.

[0072] Drying can remove the solvent in the catalyst ink and ensure uniform distribution of catalyst particles on the surface of the transition layer. Limiting the drying temperature to 70-90°C can accelerate solvent evaporation while avoiding excessive temperature that may cause catalyst particle agglomeration or structural damage. Limiting the drying time to 20-40 min ensures complete removal of the solvent. This temperature and time range can balance the needs of solvent removal and catalyst performance maintenance. For example, the drying temperature can be 70°C, 75°C, 80°C, 85°C, 90°C, etc., and the drying time can be 20 min, 25 min, 30 min, 35 min, 40 min, etc.

[0073] In some embodiments, the curing temperature is 120-160°C, and the curing time is 5-15 min.

[0074] The curing process allows the catalyst particles to better bind with the perfluorosulfonic acid resin through heating, forming a stable catalyst layer structure. Limiting the curing temperature to 120-160°C can promote the cross-linking reaction of the resin, enhancing the mechanical strength and chemical stability of the catalyst layer. Limiting the curing time to 5-15 min can ensure sufficient curing of the resin, but excessive time may cause the catalyst layer to crack or degrade in performance. This temperature and time range can ensure that the catalyst layer obtains good structural stability and durability. For example, the curing temperature can be 120°C, 130°C, 140°C, 150°C, 160°C, etc., and the curing time can be 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, etc.

[0075] In some embodiments, in the first catalyst ink, the mass ratio of Pd to Pt is (2-4):1. In the second catalyst ink, the mass ratio of Pd to Pt is 1:(2-4).

[0076] In the hydrogen inlet area, the hydrogen concentration is high, so a lower proportion of Pd can save costs. At the same time, a proper amount of Pt can ensure catalytic activity. Limiting the mass ratio of Pd to Pt in the first catalyst ink to (2-4):1 can ensure that the catalytic layer in the outlet area can still operate stably under fuel shortage conditions. Limiting the mass ratio of Pd to Pt in the second catalyst ink to 1:(2-4) can balance the cost and catalytic activity requirements to ensure the efficient operation of the catalytic layer in the inlet area. In the hydrogen outlet area, due to the decrease in hydrogen concentration, increasing the proportion of Pd can make full use of its hydrogen storage capacity to provide an additional hydrogen source for the fuel cell. For example, the mass ratio of Pd to Pt in the second catalyst ink can be 1:2, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc. The mass ratio of Pd to Pt in the first catalyst ink can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc.

[0077] In some embodiments, the sprayed first catalyst ink nozzle has the following parameters: ultrasonic frequency of 110-130 kHz, atomized particle size of 5-10 μm, nozzle spacing of 14-16 mm; the sprayed second catalyst ink nozzle has the following parameters: ultrasonic frequency of 90-110 kHz, atomized particle size of 8-15 μm, nozzle spacing of 14-16 mm.

[0078] The product prepared by the preparation method of the anti-reverse-pole anode catalytic layer is the anti-reverse-pole anode catalytic layer described above. The chemical composition and microstructure of the anti-reverse-pole anode catalytic layer prepared by the preparation method of the anti-reverse-pole anode catalytic layer can refer to the above embodiments. Since the preparation method of the anti-reverse-pole anode catalytic layer uses part or all of the technical solutions of the anti-reverse-pole anode catalytic layer embodiments, it at least has all the beneficial effects brought by the technical solutions of the anti-reverse-pole anode catalytic layer embodiments, which will not be repeated here.

[0079] Based on one overall inventive concept, the present application provides a membrane electrode, which comprises a proton exchange membrane 2, a cathode catalytic layer 3, the anti-reverse-pole anode catalytic layer 1 according to any one of the embodiments described above, and a gas diffusion layer 4, which are sequentially stacked, and the transition layer 11 of the anti-reverse-pole anode catalytic layer 1 is adjacent to the proton exchange membrane 2.

[0080] In some embodiments, the Pt / C catalyst loading of the cathode catalytic layer is 0.3-0.5 mg Pt / cm 2 . Pt / cm 2 .

[0081] Membrane electrode is the core component of fuel cell, which integrates proton exchange membrane, cathode catalyst layer, anti-reverse anode catalyst layer and gas diffusion layer, etc. components together to form a complete electrochemical reaction system. By optimizing the structure and performance of each component, the overall performance and stability of fuel cell can be improved. Among them, the anti-reverse anode catalyst layer adopts an innovative design, and the transition layer is arranged adjacent to the proton exchange membrane, which brings many advantages: (1) Proton conduction efficiency is improved: the close contact between the transition layer and the proton exchange membrane helps the rapid conduction of protons between them. Since the proton exchange membrane is the key path of proton migration in fuel cell, optimizing this interface can significantly reduce the resistance of proton conduction, thereby improving the overall efficiency of the cell.

[0082] (2) Electrochemical reaction optimization: the special design of the anti-reverse anode catalyst layer, including the gradient distribution of Pd / C and Pt / C hybrid catalysts, and the hydrogen storage capacity of Pd, makes the utilization of hydrogen more efficient. The transition layer as a bridge between the catalyst layer and the proton exchange membrane can ensure that the electrochemical reaction is evenly carried out in a wider area, reducing the problem of local overheating and uneven reaction.

[0083] (3) Stability and durability are enhanced: the transition layer is usually composed of high-stability materials, such as Pd and Pt nanoparticles deposited on the p-WO3 film, which not only improves the mechanical strength of the catalyst layer, but also enhances its ability to resist reverse polarity. The adjacent arrangement with the proton exchange membrane further protects the membrane structure and prolongs the service life of the membrane electrode.

[0084] (4) Gas management and water management optimization: the gas diffusion layer is an important part of the membrane electrode, responsible for uniform gas distribution and effective water management. The synergistic effect of the anti-reverse anode catalyst layer and the gas diffusion layer ensures efficient utilization of hydrogen and timely discharge of water, preventing water flooding and maintaining stable operation of the cell.

[0085] Based on a general inventive concept, the present application provides a fuel cell comprising the anti-reverse anode catalyst layer according to any one of the embodiments described above, or the membrane electrode described above.

[0086] The fuel cell described in the present application realizes significant progress in the field of fuel cell technology by using the anti-reverse anode catalyst layer according to any one of the embodiments described above, or the membrane electrode comprising the anti-reverse anode catalyst layer described above. The main features and advantages of the fuel cell are as follows: (1) Improve hydrogen utilization: The core of fuel cells lies in the efficient utilization of hydrogen. The anti-reverse anode catalyst layer in this application solves the problem of insufficient hydrogen supply when fuel is short through the storage and release mechanism of hydrogen in the Pd lattice and the design of increasing Pd content gradient along the hydrogen flow direction. This innovative design ensures uniform distribution and efficient reaction of hydrogen in the catalyst layer, thereby improving the overall utilization of hydrogen.

[0087] (2) Enhance anti-reverse performance: Reverse phenomenon is a common problem during the operation of fuel cells, which can cause battery performance degradation or even damage. The anti-reverse anode catalyst layer in this application significantly enhances the ability of the catalyst layer to resist reverse phenomenon by optimizing the catalyst composition and structure design. Even in the case of fuel shortage or load mutation, the battery can maintain stable operation.

[0088] (3) Improve battery efficiency and output performance: The use of specially designed membrane electrode design, including proton exchange membrane, cathode catalyst layer, anti-reverse anode catalyst layer and gas diffusion layer, realizes efficient electrochemical reaction and rapid proton conduction. This directly improves the efficiency and output performance of fuel cells, enabling them to meet higher power density and longer endurance requirements.

[0089] (4) Extend service life and reduce maintenance cost: Long-term stable operation and low-cost maintenance of fuel cells are the key to commercial application. The anti-reverse anode catalyst layer and membrane electrode design in this application effectively extend the service life of fuel cells by improving the stability and durability of the catalyst layer and optimizing gas and water management. At the same time, it reduces the damage and repair needs of the battery caused by reverse phenomenon, reducing the overall maintenance cost.

[0090] The fuel cell described in this application realizes significant improvement in hydrogen utilization, anti-reverse performance, battery efficiency and output performance, and service life and maintenance cost by using innovative anti-reverse anode catalyst layer and membrane electrode design.

[0091] In summary, the anti-reverse anode catalyst layer and preparation method, membrane electrode and fuel cell provided by the embodiments of the application have the following advantages: (1) Significantly improve hydrogen utilization: By designing a heterogeneous grid distribution gradient anode catalyst layer with different Pd / C content, hydrogen can be automatically supplemented at the hydrogen outlet position, effectively reducing the emission of unreacted hydrogen, thereby improving the utilization of hydrogen.

[0092] (2) Enhance the anti-reverse performance: the introduction of ultra-thin transition layer, forming a "trinity" protective barrier (Pd hydrogen storage, p-WO3 electronic transmission enhancement, sulfonic acid group proton fast transport), in the reverse pole of the initial activation of WO3 redox reaction, sacrificial consumption of reverse current, protect Pt / C main catalyst, significantly improve the stability of fuel cell in fuel shortage conditions.

[0093] (3) Improve the efficiency and output performance of the battery: the p-WO3 film in the transition layer and the sulfonic acid group enhance the transmission performance of electrons and protons, respectively, while the high-activity Pt / C and Pd / C catalysts in the gradient anode catalyst layer promote the oxidation reaction of hydrogen, which improves the reaction efficiency and output performance of the fuel cell.

[0094] (4) Prolong the service life and reduce the maintenance cost: WO3 in the transition layer preferentially undergoes redox reaction in the initial stage of reverse pole, protecting the main catalyst Pt / C from damage; the gradient design in the gradient anode catalyst layer reduces the reverse phenomenon caused by fuel shortage, thereby prolonging the service life of the fuel cell. At the same time, the gradient design helps to save expensive Pd resources, reducing the manufacturing cost and maintenance cost of the fuel cell.

[0095] (5) Innovative preparation method: the transition layer is synthesized by plasma enhanced atomic layer deposition method, which ensures the uniform distribution of Pt and Pd on a nanoscale, and realizes maximum catalytic activity under the premise of using a small amount of noble metal, with the advantages of low cost, high performance and long durability.

[0096] The application will be further described in conjunction with specific examples. It should be understood that these examples are only used to illustrate the application and not to limit the scope of the application. The experimental methods in the following examples are not specified, which are usually determined according to the industry standard. If there is no corresponding industry standard, it is determined according to the general international standard, the conventional condition, or according to the condition suggested by the manufacturer.

[0097] Example 1 The present embodiment provides a preparation method of an anti-reverse anode catalyst layer, which can include the following steps: S11, 2000 mg of WO3 nano powder is mixed with 4000 mg of anhydrous ethanol and ultrasonically dispersed for 30 min to obtain a WO3 slurry; the WO3 slurry is coated on the surface of a polytetrafluoroethylene film with a thickness of 25 μm using a doctor blade, and then dried in an oven at 70°C for 20 h to obtain a WO3 film; S21, the WO3 film is subjected to Ar plasma surface treatment to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the Ar plasma power is 200 W, the flow rate of Ar is 20 sccm, and the chamber pressure is set to 30 mTorr; S31, the p-WO3 thin film was placed in a deposition chamber of a custom-made plasma-enhanced atomic layer deposition device (PEALD), and the p-WO3 thin film was cut into a sample of 5.0 x 5.0 cm 2 Under vacuum conditions, a precursor pulse (1 s) - Ar purge (100 s) - O2 plasma (20 s) - Ar purge (100 s) was used as a precursor of Pd and Pt, which was composed of PEALD and palladium chloride (PdCl2), trimethyl (methylcyclopentadienyl) platinum (IV) (MeCpPtMe3). The precursor was maintained at 75°C, and the deposition temperature was 140°C. An O2 plasma was generated using a radio frequency plasma power of 250 W with O2 (45 sccm) to obtain a deposition layer containing Pd nanoparticles and Pt nanoparticles.

[0098] S41, after the deposition of Pd and Pt, a micro pipette was used to disperse 20 μL of a solution with a volume ratio of 1:15 on the deposition layer, which was composed of 10 wt% water-based Nafion ionomer (DuPont, USA) and ethanol. After drying in an oven at 70ºC for 24 h, a transition layer with a thickness of 0.8 μm was obtained, in which the mass ratio of Pd nanoparticles to Pt nanoparticles was 1:1.5.

[0099] S51, Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin, and solvent were mixed to obtain a first catalyst ink and a second catalyst ink, respectively. A double-jet ultrasonic atomization spraying system was used to spray the first catalyst ink and the second catalyst ink on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode. During the spraying process, the spraying flow rate of the first catalyst ink increased from 0 to the maximum flow rate, and the spraying flow rate of the second catalyst ink decreased from the maximum flow rate to 0, so as to form a gradient anode catalyst layer with an increasing Pd content and a decreasing Pt content along the flow direction of hydrogen in the membrane electrode on one side of the transition layer. The gradient anode catalyst layer was dried and cured to obtain a reverse-pole-resistant anode catalyst layer. The drying temperature was 80°C, and the drying time was 30 min. The curing temperature was 140°C, and the curing time was 10 min. In the first catalyst ink, the mass ratio of Pd to Pt was 3:1; in the second catalyst ink, the mass ratio of Pd to Pt was 1:3. In the gradient anode catalyst layer, the mass ratio of Pd to Pt at the starting position was 1:3, and the mass ratio of Pd to Pt at the end position was 3:1 along the flow direction of hydrogen in the membrane electrode. The average thickness of the gradient anode catalyst layer was 3 μm.

[0100] For further illustration, the more specific experimental procedure of S51 step is as follows: 1. Materials and equipment (1) Material list: First catalyst ink (high Pd ink): Pt / C (20% Pt, Johnson Matthey) + Pd / C (30% Pd, Tanaka) mixed catalyst (Pd: Pt mass ratio 3: 1); Second catalyst ink (low Pd ink): Pt / C (20% Pt, Johnson Matthey) + Pd / C (30% Pd, Tanaka) mixed catalyst (Pd: Pt mass ratio 1: 3); Perfluorosulfonic acid resin (Nafion D521, 5 wt% solution); Isopropyl alcohol / deionized water mixed solvent (volume ratio 3: 1); (2) Equipment list: Double-jet ultrasonic atomization spraying system; Three-axis motion platform (precision ± 10 μm, repeatability ± 5 μm); Real-time thickness monitor; High-temperature vacuum drying oven.

[0101] 2. Catalyst ink preparation Ink formula (two inks are prepared synchronously): High Pd ink: Pt / C (80 mg) + Pd / C (240 mg) + Nafion D521 (200 μL) + solvent 10 mL; Low Pd ink: Pt / C (240 mg) + Pd / C (80 mg) + Nafion D521 (200 μL) + solvent 10 mL; Ultrasonic dispersion: 40 kHz ultrasonic treatment for 2 h (power 200 W, ice bath temperature control < 25℃); Viscosity control: adjust to 30 mPa·s~40 mPa·s (25℃), meet the atomization requirements.

[0102] 3. Double-jet spraying system settings (1) Jet parameters: Jet A (high Pd ink): ultrasonic frequency 120 kHz, atomization particle size 5 μm~10 μm, flow rate ≤5 mL / min; Jet B (low Pd ink): ultrasonic frequency 100 kHz, atomization particle size 8 μm~15 μm, flow rate ≤5 mL / min; Jet spacing: 15 mm (to avoid cross contamination); Jet spraying width: 5 mm; Carrier gas pressure: 0.15 MPa (nitrogen purity > 99.999%); (2) Motion trajectory program (based on H2 flow channel serpentine path): Path design: The serpentine flow channel is divided into continuous line segment units (length 50 mm, width 5 mm), and 10 spraying zones are divided along the H2 flow direction (X axis).

[0103] (3) Gradient control logic: - Entrance zone: X = 0-5 mm, use spray head B with a proportion of 100% and spray head A with a proportion of 0%; - Transition zone: 5 < X < 45 mm, gradually increase the proportion of spray head A from 0% to 100% (while reducing the proportion of spray head B) - Exit zone: X = 45-50 mm, use spray head B with a proportion of 0% and spray head A with a proportion of 100% (4) Motion control code (G-code example): G01 X0 Y0 F1000; Start point positioning WHILE X<=50; Move along X axis IF 0≤X≤5mm; SPRAY_B ON; Only turn on low Pd spray head ELIF 5mm<X<45mm; SPRAY_A ON; High Pd spray head opening proportion = (X-5) / 40 x 100% SPRAY_B ON; Low Pd spray head opening proportion = [1 - (X-5) / 40 ]x 100% ELSE 45≤X≤50 mm: SPRAY_A ON; Only turn on high Pd spray head END Real-time feedback adjustment: (5) Dynamically adjust spray head flow rate through thickness monitor data: If the local thickness deviation is > 5%, trigger the PID control algorithm to adjust the corresponding spray head flow rate (adjustment range ±0.05 mL / min).

[0104] 4. Spraying operation steps (1) Substrate pretreatment: GDL is placed in an oxygen plasma cleaning machine (30 W, 5 minutes) for treatment, and the contact angle is reduced from 120° to <20°.

[0105] (2) Spraying process: Substrate temperature control: 60°C (heating table constant temperature); Spraying distance: 30 mm (spray head to GDL surface); Single layer spray number: 3 times (alternate direction: 0°→90°→45°); Total loading control: 0.4 mg Pt / cm2(by inkjet time back calculation).

[0106] (3) Drying and curing: Stage 1: 80°C vacuum drying for 30 minutes (solvent removal); Stage 2: 140°C heat treatment for 10 minutes (Nafion resin microphase separation).

[0107] Example 2 The present embodiment provides a preparation method of an anti-reverse anode catalyst layer, which can include the following steps: S11, 2000 mg of WO3 nano powder is mixed with 2000 mg of absolute ethanol and ultrasonically dispersed for 60 min to obtain a WO3 slurry; the WO3 slurry is coated on the surface of a polytetrafluoroethylene film with a thickness of 25 μm using a doctor blade, and then dried in an oven at 80°C for 10 h to obtain a WO3 film; S21, the WO3 film is subjected to Ar plasma surface treatment to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the Ar plasma power is 180 W, the flow rate of Ar is 30 sccm, and the chamber pressure is set to 25 mTorr; S31, the p-WO3 film is placed in a deposition chamber of a customized plasma-enhanced atomic layer deposition device (PEALD), and the p-WO3 film is cut into a specimen with a size of 5.0×5.0 cm 2 The precursor pulse (2 s) - Ar purge (120 s) - O2 plasma (30 s) - Ar purge (120 s) is used as the precursor of Pd and Pt, which is composed of PEALD and palladium chloride (PdCl2), trimethyl (methylcyclopentadienyl) platinum (IV) (MeCpPtMe3). The precursor is kept at 85°C, and the deposition temperature is 160°C. The O2 plasma with a radio frequency plasma power of 250 W is used to generate O2 plasma (60 sccm) to obtain a deposition layer containing Pd nanoparticles and Pt nanoparticles.

[0108] S41, after the deposition of Pd and Pt, a micro pipette is used to disperse 20 μL of a solution with a volume ratio of 1:20 on the deposition layer, together with 10 wt% of water-based Nafion ionomer (DuPont, USA) and ethanol. Dry in an oven at 80ºC for 24 h to obtain a transition layer with a thickness of 0.7 μm, in which the mass ratio of Pd nanoparticles to Pt nanoparticles is 1:2.

[0109] S51, mixing Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin and solvent to obtain first catalyst ink and second catalyst ink respectively; using double-jet ultrasonic atomization spraying system, spraying the first catalyst ink and the second catalyst ink on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and during the spraying process, the spraying flow of the first catalyst ink increases from 0 to the maximum flow, and the spraying flow of the second catalyst ink decreases from the maximum flow to 0, to form a gradient anode catalyst layer with increasing Pd content and decreasing Pt content along the flow direction of hydrogen in the membrane electrode on one side of the transition layer; drying and curing the gradient anode catalyst layer to obtain an anti-reverse anode catalyst layer. The drying temperature is 70°C, and the drying time is 40 min. The curing temperature is 120°C, and the curing time is 15 min. In the first catalyst ink, the mass ratio of Pd to Pt is 2:1; in the second catalyst ink, the mass ratio of Pd to Pt is 1:2. In the gradient anode catalyst layer, along the flow direction of hydrogen in the membrane electrode, the mass ratio of Pd to Pt at the starting position is 1:2, and the mass ratio of Pd to Pt at the end position is 2:1. The average thickness of the gradient anode catalyst layer is 4μm.

[0110] Example 3 The present embodiment provides a preparation method of an anti-reverse anode catalyst layer, which can include the following steps: S11, mixing 2000mg WO3 nano powder with 20000mg anhydrous ethanol and ultrasonic dispersion for 45min to obtain WO3 slurry; using a doctor blade to coat the WO3 slurry on the surface of a polytetrafluoroethylene film with a thickness of 25μm, and then drying in an oven at 60°C for 30h to obtain a WO3 film; S21, Ar plasma surface treatment of the WO3 film to generate oxygen vacancies in the WO3 lattice to obtain a p-WO3 film; wherein the Ar plasma power is 200W, the flow rate of Ar is 10sccm, and the chamber pressure is set to 30mTorr; S31, placing the p-WO3 film in a customized plasma enhanced atomic layer deposition device (PEALD) deposition chamber, cutting the p-WO3 film into 5.0×5.0 cm 2The sample was prepared in a vacuum condition. PEALD and precursor pulse (0.1 s) - Ar purge (60 s) - O2 plasma (10 s) - Ar purge (60 s) were used as the precursor of Pd and Pt, which consisted of PEALD and palladium chloride (PdCl2), trimethyl (methylcyclopentadienyl) platinum (IV) (MeCpPtMe3). The precursor was kept at 65 °C, and the deposition temperature was 120 °C. O2 plasma was generated using O2 (45 sccm) with a radio frequency plasma power of 250 W, and a deposition layer containing Pd nanoparticles and Pt nanoparticles was obtained.

[0111] S41, after the deposition of Pd and Pt, 20 μL of a solution with a volume ratio of 1:20 was dispersed on the deposition layer using a micro pipette, 10 wt% water-based Nafion ionomer (DuPont, USA) and ethanol. After drying in an oven at 60 °C for 24 h, a transition layer with a thickness of 0.9 μm was obtained, in which the mass ratio of Pd nanoparticles to Pt nanoparticles was 1:1.

[0112] S51, the Pt / C catalyst, the Pd / C catalyst, the perfluorosulfonic acid resin and the solvent were mixed to obtain a first catalyst ink and a second catalyst ink, respectively; using a double-nozzle ultrasonic atomization spraying system, the first catalyst ink and the second catalyst ink were sprayed on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and during the spraying process, the spraying flow rate of the first catalyst ink increased from 0 to the maximum flow rate, and the spraying flow rate of the second catalyst ink decreased from the maximum flow rate to 0, so as to form a gradient anode catalyst layer with increasing Pd content and decreasing Pt content along the flow direction of hydrogen in the membrane electrode on one side of the transition layer; the gradient anode catalyst layer was dried and cured to obtain an anti-reverse anode catalyst layer. The drying temperature was 90 °C, and the drying time was 20 min. The curing temperature was 160 °C, and the curing time was 5 min. In the first catalyst ink, the mass ratio of Pd to Pt was 4:1; in the second catalyst ink, the mass ratio of Pd to Pt was 1:4. In the gradient anode catalyst layer, along the flow direction of hydrogen in the membrane electrode, the mass ratio of Pd to Pt at the starting position was 1:4, and the mass ratio of Pd to Pt at the end position was 4:1. The average thickness of the gradient anode catalyst layer was 2 μm.

[0113] Example 4 Based on the anti-reverse anode catalyst layer obtained in Example 1, this embodiment provides a method for preparing a fuel cell, comprising the following steps: Pt / C slurry was prepared by mixing 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) for 15 min. The Pt / C slurry was coated on the surface of a polytetrafluoroethylene film with a thickness of 25 μm using a 150 μm wire bar, and then dried at 70°C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C catalyst loading of the cathode catalyst layer was 0.4 mg Pt / cm 2 ; A membrane electrode with an active area of 20 cm 2 was prepared by hot-pressing a proton exchange membrane (Gore Gore 8 μm membrane), the anti-reversal anode catalyst layer of Example 1 and the Pt / C cathode catalyst layer at 130°C and 380 kPa; the obtained membrane electrode was assembled with a diffusion layer (Toray GDL gas diffusion layer 055) and a sealing ring into a single cell test fixture, thereby obtaining a single cell.

[0114] Example 5 Based on the anti-reversal anode catalyst layer obtained in Example 2, this embodiment provides a method for preparing a fuel cell, comprising the following steps: Pt / C slurry was prepared by mixing 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water-based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) for 15 min. The Pt / C slurry was coated on the surface of a polytetrafluoroethylene film with a thickness of 25 μm using a 150 μm wire bar, and then dried at 70°C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C catalyst loading of the cathode catalyst layer was 0.4 mg Pt / cm 2 ; A membrane electrode with an active area of 20 cm 2 was prepared by hot-pressing a proton exchange membrane (Gore Gore 8 μm membrane), the anti-reversal anode catalyst layer of Example 2 and the Pt / C cathode catalyst layer at 130°C and 380 kPa; the obtained membrane electrode was assembled with a diffusion layer (Toray GDL gas diffusion layer 055) and a sealing ring into a single cell test fixture, thereby obtaining a single cell.

[0115] Example 6 Based on the anti-reversal anode catalyst layer obtained in Example 3, this embodiment provides a method for preparing a fuel cell, comprising the following steps: A Pt / C slurry was prepared by mixing 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) for 15 min. The Pt / C slurry was coated onto the surface of a polytetrafluoroethylene membrane with a thickness of 25 μm using a 150 μm wire bar and dried at 70 °C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C catalyst loading of the cathode catalyst layer was 0.5 mg Pt / cm 2 ; A membrane electrode with an active area of 20 cm 2 was prepared by hot pressing a proton exchange membrane (Gore Select® 8 μm membrane), the anti-reverse electrode anode catalyst layer of Example 3, the Pt / C cathode catalyst layer at 130 °C and 380 kPa; the obtained membrane electrode was assembled with a diffusion layer (Toray GDL gas diffusion layer 055), a gasket into a single cell test fixture to obtain a single cell.

[0116] Comparative Example 1 This comparative example provides a method for preparing a conventional fuel cell with Pt / C catalysts for both the anode and the cathode, which can include the following steps: A Pt / C slurry was prepared by mixing 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) for 15 min. The Pt / C slurry was coated onto the surface of a polytetrafluoroethylene membrane with a thickness of 25 μm using a 150 μm wire bar and dried at 70 °C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C catalyst loading of the cathode catalyst layer was 0.5 mg

[0117] A Pt / C slurry was prepared by mixing 530 mg of 40 wt% Pt / C, 2600 mg of 10 wt% water based Nafion ionomer and 8000 mg of isopropyl alcohol (IPA) for 15 min. The Pt / C slurry was coated onto the surface of a polytetrafluoroethylene membrane with a thickness of 25 μm using a 150 μm wire bar and dried at 70 °C for 24 h to obtain a Pt / C cathode catalyst layer; the Pt / C catalyst loading of the cathode catalyst layer was 0.5 mg

[0118] The Pt / C anode catalyst layer and the Pt / C cathode catalyst layer were cut into a cell area of 5 x 5 cm 2 A membrane electrode was prepared by hot pressing a proton exchange membrane (Gore Select® 8 μm membrane), the Pt / C anode catalyst layer, the Pt / C cathode catalyst layer at 130 °C and 380 kPa; the obtained membrane electrode was assembled with a diffusion layer (Toray GDL gas diffusion layer 055), a gasket into a single cell test fixture to obtain a single cell.

[0119] Comparative Example 2 This comparative example is based on the disclosure of Example 4 with the following modifications: The anode catalytic layer only contains the transition layer and does not contain the gradient anode catalyst layer.

[0120] Comparative Example 3 This comparative example is based on the disclosure of Example 4 with the following modifications: The anode catalytic layer only contains the gradient anode catalyst layer and does not contain the transition layer.

[0121] Comparative Example 4 This comparative example is based on the disclosure of Example 5 with the following modifications: The Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin and solvent are mixed to obtain a catalyst ink; the catalyst ink is sprayed on the surface of the transition layer to form an anode catalyst layer; the anode catalyst layer is dried and cured to obtain an anti-reverse anode catalyst layer. The drying temperature is 90°C and the drying time is 20 min. The curing temperature is 160°C and the curing time is 5 min. In the catalyst ink, the mass ratio of Pd to Pt is 1:1.5.

[0122] Comparative Example 5 This comparative example is based on the disclosure of Example 5 with the following modifications: The Pd / C catalyst, perfluorosulfonic acid resin and solvent are mixed to obtain a catalyst ink; the catalyst ink is sprayed on the surface of the transition layer to form an anode catalyst layer; the anode catalyst layer is dried and cured to obtain an anti-reverse anode catalyst layer. The drying temperature is 90°C and the drying time is 20 min. The curing temperature is 160°C and the curing time is 5 min.

[0123] The fuel cell single cells obtained in Examples 4-6 and Comparative Examples 1-5 are subjected to electrochemical performance determination, and the results are shown in Table 1.

[0124] Table 1 Electrochemical performance of the fuel cell single cells obtained in Examples 4-6 and Comparative Examples 1-5

[0125] Figure 3 Polarization curve of the fuel cell single cell provided for Example 4 and Comparative Example 1.

[0126] In Figure 3The single cell test polarization curve of the following four groups of experiments was determined: the traditional membrane electrode assembly (MEA) in Comparative Example 1 using a Pt / C anode, with pure hydrogen as the anode gas; the traditional MEA in Comparative Example 1 also using a Pt / C anode, with simulated reforming gas (40% H2, 5% H2O and 55% N2) as the anode gas; the Pt / C+Pd / C gradient anode membrane electrode in Example 4, with pure hydrogen as the anode gas; and the Pt / C+Pd / C gradient anode membrane electrode in Example 4, with simulated reforming gas (40% H2, 5% H2O and 55% N2) as the anode gas.

[0127] From the test results of Figure 3 It can be seen from the test results that when the anode is in a pure hydrogen environment, the performance of the Pt / C+Pd / C gradient membrane electrode of Example 4 is similar to that of the Pt / C catalyst membrane electrode of Comparative Example 1; when the anode is in a reforming gas environment, the Pt / C+Pd / C gradient membrane electrode of Example 4 is less affected by the decrease in hydrogen content, and the performance of the Pt / C catalyst membrane electrode of Comparative Example 1 decreases significantly. This shows that under low hydrogen concentration (40% H2) and inert gas dilution conditions, the gradient structure membrane electrode exhibits stronger resistance to mass transfer polarization, verifying the practical advantages of the Pt / C+Pd / C gradient anode membrane electrode in low hydrogen and complex component gas source environments.

[0128] Figure 4 The fuel cell single cell simulation reverse polarization comparison chart provided for Example 4 and Comparative Example 1 of the present application.

[0129] From the test results of Figure 4 It can be seen that the water electrolysis platform time of Example 4 is significantly longer than that of Comparative Example 1, indicating that the catalyst and membrane electrode assembly of Example 4 are more stable in water electrolysis reaction and have better reverse polarization resistance.

[0130] In addition, one or more technical solutions in the embodiments of the present application have at least the following technical effects or advantages: In the embodiments of the present application, an alternative electrode design is proposed, which uses plasma surface treatment technology to introduce ultra-thin Pt / p-WO3 and Pd / p-WO3 ultra-thin transition layers, preferentially activates the redox reaction of WO3 at the initial stage of reverse polarization, and uses a spray deposition method to prepare a Pd-assisted gradient anode catalyst layer with a flow path distribution, which can actively prevent the membrane electrode of a proton exchange membrane fuel cell from being reversed at the anode during actual fuel cell operation, thereby improving the stability under fuel shortage.

[0131] In the embodiments of the present application, an ultrathin transition layer is introduced at the interface between the anode catalytic layer and the proton exchange membrane. Pt and Pd nanoparticles are deposited on the p-WO3 ultrathin transition layer by using plasma surface treatment technology. The layer forms a “trinity” protective barrier through the hydrogen storage buffer of Pd, the enhancement of the electron conduction of WO3 and the rapid proton transmission of the sulfonic acid group, preferentially activates the redox reaction of WO3 at the initial stage of reverse polarity, and sacrificially consumes the reverse polarity current to protect the Pt / C main catalyst.

[0132] In the embodiments of the present application, a gradient anode catalytic layer with different Pd / C content hybrid is designed to automatically supplement hydrogen at the position close to the outlet where fuel shortage may occur, further preventing the occurrence of reverse polarity. Ultimately, compared with commercial Pt / C, it can show the advantages of low cost, high performance, long durability and anti-reverse polarity ability under various working conditions.

[0133] In the embodiments of the present application, the plasma-enhanced atomic layer deposition method realizes high-purity deposition of Pt and Pd under low-temperature conditions, and the nanoscale uniform distribution reduces the amount of noble metals while maintaining catalytic activity, thereby significantly reducing the cost. At the same time, the sacrificial protection of WO3 reduces the dependence on high-cost OER catalysts (such as IrO2), and the hydrogen storage function of Pd optimizes the material cost while ensuring performance.

[0134] In the embodiments of the present application, the p-WO3 substrate has higher oxidation resistance than the traditional carbon carrier (such as Vulcan XC-72), which delays the corrosion of the carrier during the reverse polarity process and prolongs the service life of the catalytic layer. At the same time, the gradient distribution of the hybrid catalyst layer reduces local hot spots and stress concentration, reduces the risk of mechanical damage to the membrane electrode, and improves the overall durability.

[0135] In the embodiments of the present application, the Pd lattice releases the stored hydrogen through the hydrogen storage / hydrogen release characteristics of the Pd-H bond when the fuel is short, prolongs the water electrolysis platform time, and avoids the oxidation of the carbon carrier and the failure of the catalyst caused by reverse polarity.

[0136] The above is only a specific embodiment of the present application, which enables those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied herein.

Claims

1. An anti-reversal anode catalyst layer (1), comprising: a transition layer (11) comprising a p-WO3 film, a deposition layer deposited on at least part of the surface of the p-WO3 film, and an ionic polymer containing sulfonic acid groups dispersed in the deposition layer; the deposition layer containing Pd nanoparticles and Pt nanoparticles; and a gradient anode catalyst layer (12) disposed on one side of the transition layer (11) and containing Pd / C and Pt / C hybrid catalysts, the mass content of Pd in the Pd / C and Pt / C hybrid catalysts increasing and the mass content of Pt in the Pd / C and Pt / C hybrid catalysts decreasing along the flow direction of hydrogen in the membrane electrode.

2. The anti-kathodic anode catalytic layer of claim 1, wherein, In the transition layer (11), the mass ratio of the Pd nanoparticles to the Pt nanoparticles is 1:(1-2).

3. The anti-kathodic anode catalytic layer of claim 2, wherein, The thickness of the transition layer (11) is less than or equal to 1.0 μm.

4. The anti-kathodic anode catalytic layer according to any one of claims 1 to 3, characterized in that, In the gradient anode catalyst layer (12), the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the starting position along the flow direction of hydrogen in the membrane electrode is 1:(2-4).

5. The anti-kathodic anode catalytic layer of claim 4, wherein, In the gradient anode catalyst layer (12), the mass ratio of the Pd nanoparticles to the Pt nanoparticles at the end position along the flow direction of hydrogen in the membrane electrode is (2-4):

1.

6. The anti-kathodic anode catalytic layer of claim 5, wherein, The thickness of the gradient anode catalyst layer (12) is 2 μm-4 μm.

7. A method for preparing the anti-reversal anode catalyst layer according to any one of claims 1-6, the method comprising: obtaining a WO3 film; activating the WO3 film to generate oxygen vacancies in the WO3 lattice of the WO3 film, thereby obtaining a p-WO3 film; depositing Pd nanoparticles and Pt nanoparticles on at least part of the surface of the p-WO3 film, thereby obtaining a deposition layer; dispersing an ionic polymer containing sulfonic acid groups into the deposition layer, thereby obtaining a transition layer; spraying a hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, gradually increasing the mass content of Pd in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst and gradually decreasing the mass content of Pt in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst along the flow direction of hydrogen in the membrane electrode, so as to form a gradient anode catalyst layer with increasing mass content gradient of Pd and decreasing mass content gradient of Pt along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, thereby obtaining an anti-reversal anode catalyst layer.

8. The method of claim 7, wherein, The obtaining of the WO3 film comprises: mixing WO3 nano-powder and anhydrous ethanol to obtain a WO3 slurry; coating the WO3 slurry on a base film and drying, thereby obtaining a WO3 film.

9. The method of claim 8, wherein, The mass ratio of the WO3 nano-powder to the anhydrous ethanol is 1:(1-10).

10. The method of claim 7, wherein, The activation is performed by plasma surface treatment.

11. The method of claim 7, wherein, The deposition of Pd nanoparticles and Pt nanoparticles on at least part of the surface of the p-WO3 film to obtain a deposition layer comprises: adsorbing Pd precursor and Pt precursor to the surface of the p-WO3 film under vacuum condition to obtain p-WO3 film containing Pd precursor and Pt precursor, wherein the Pd precursor is palladium chloride and the Pt precursor is trimethyl(methylcyclopentadienyl) platinum; purging the p-WO3 film containing Pd precursor and Pt precursor in inert gas; carrying out adsorption reaction of oxygen precursor with Pd precursor and Pt precursor in the p-WO3 film to obtain deposition layer containing Pd nanoparticles and Pt nanoparticles, wherein the oxygen precursor is O2 plasma.

12. The method according to any one of claims 7 to 11, characterized in that, spraying the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and gradually increasing the mass content of Pd and gradually reducing the mass content of Pt in the hybrid catalyst ink containing Pt / C catalyst and Pd / C catalyst along the flow direction of hydrogen in the membrane electrode to form a gradient anode catalyst layer with gradually increasing mass content of Pd and gradually decreasing mass content of Pt along the flow direction of hydrogen in the membrane electrode on one side of the transition layer, thereby obtaining a reverse-polarity-resistant anode catalyst layer, comprising: mixing Pt / C catalyst, Pd / C catalyst, perfluorosulfonic acid resin and solvent to obtain first catalyst ink and second catalyst ink, respectively, wherein the Pd concentration of the first catalyst ink is greater than the Pd concentration of the second catalyst ink, and the Pt concentration of the first catalyst ink is less than the Pt concentration of the second catalyst ink; using a double-nozzle ultrasonic atomization spraying system, spraying the first catalyst ink and the second catalyst ink on the surface of the transition layer along the flow direction of hydrogen in the membrane electrode, and during the spraying process, the spraying flow of the first catalyst ink is increased and the spraying flow of the second catalyst ink is decreased, so as to form a gradient anode catalyst layer with gradually increasing mass content of Pd and gradually decreasing mass content of Pt along the flow direction of hydrogen in the membrane electrode on one side of the transition layer; drying and curing the gradient anode catalyst layer to obtain a reverse-polarity-resistant anode catalyst layer.

13. The method of claim 12, wherein, The drying temperature is 70-90°C, and the drying time is 20-40 min.

14. The method of claim 12, wherein, The curing temperature is 120-160°C, and the curing time is 5-15 min.

15. The method of claim 12, wherein, In the first catalyst ink, the mass ratio of Pd to Pt is (2-4):

1. In the second catalyst ink, the mass ratio of Pd to Pt is 1:(2-4).

16. A membrane electrode, comprising a proton exchange membrane (2), a cathode catalyst layer (3), a reverse-polarity-resistant anode catalyst layer (1) according to any one of claims 1 to 6, and a gas diffusion layer (4) arranged in sequence, wherein the transition layer (11) of the reverse-polarity-resistant anode catalyst layer (1) is adjacent to the proton exchange membrane (2).

17. The membrane electrode of claim 16, wherein, The Pt / C catalyst loading of the cathode catalytic layer is 0.3 mg Pt / cm 2 ~ 0.5 mg Pt / cm 2 .

18. A fuel cell comprising the anti-reversal anode catalytic layer of any one of claims 1 to 6, or the membrane electrode of claim 16 or 17.